A virtual element and interface based concurrent multiscale method for failure analysis of quasi brittle heterogeneous composites. (15th October 2020) - Rivarola, F. López; Labanda, N.A.; Benedetto, M.F.; Etse, G.
Highlights: A concurrent multi-scale model based in an augmented Lagrangian formulation and the virtual element method (VEM) is proposed. The formulation and VEM discretization is presented and discussed. Explicit discontinuities are considered to simulate the damage in the micro-scale. Validations of our proposal with experimental results are shown. Other numerical applications to demonstrate the model are also introduced. Abstract: The use of multiscale schemes for computational failure evaluations of quasi-brittle composites, particularly concrete, has become a promising challenge for evaluating the complex degradation mechanisms at different scales of observations. In the framework of standard finite element procedures, both concurrent and semi-concurrent multiscale procedures have so far been considered for analysing failure behaviour of quasi-brittle materials. When it comes to composite materials like concrete with heterogeneous meso-structures due to the presence of highly irregular inclusions regarding both size and geometry, the material meso-structure critically determines the macroscopic mechanical properties and thus the mechanical response to external loading. In this work a concurrent multiscale method is proposed for numerical analysis of the failure behaviour of heterogeneous and quasi-brittle materials like concrete. This is based on combining a discretization based on the Virtual Element Method (VEM) and Interface Elements (IEs) in the framework of the discrete crack approach using a mixed augmented Lagrangian for the interfaces. Mesoscale numerical simulations of 3 point beam specimens are presented to assess the quality of the proposed concurrent multiscale procedure to accurately and effectively capture the relevant features of their failure mechanisms, highlighting the advantages of using the VEM technology.